Liraglutide suppresses tau hyperphosphorylation, amyloid beta accumulation through regulating neuronal insulin signaling and BACE-1 activity - Salinee Jantrapirom (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Neuronal insulin resistance is a significant feature of Alzheimer’s disease (AD). Accumulated evidence has revealed the possible neuroprotective mechanisms of antidiabetic drugs in AD. Liraglutide, a glucagon-like peptide-1 (GLP-1) analog and an antidiabetic agent, has a benefit in improving a peripheral insulin resistance. However, the neuronal effect of liraglutide on the model of neuronal insulin resistance with Alzheimer’s formation has not been thoroughly investigated. The present study discovered that liraglutide alleviated neuronal insulin resistance and reduced beta-amyloid formation and tau hyperphosphorylation in a human neuroblostoma cell line, SH-SY5Y. Liraglutide could effectively reverse deleterious effects of insulin overstimulation. In particular, the drug reversed the phosphorylation status of insulin receptors and its major downstream signaling molecules including insulin receptor substrate 1 (IRS-1), protein kinase B (AKT), and glycogen synthase kinase 3 beta (GSK-3β). Moreover, liraglutide reduced the activity of beta secretase 1 (BACE-1) enzyme, which then decreased the formation of beta-amyloid in insulinresistant cells. This indicated that liraglutide can reverse the defect of phosphorylation status of insulin signal transduction but also inhibit the formation of pathogenic Alzheimer’s proteins like Aβ in neuronal cells. We herein provided the possibility that the liraglutide-based therapy may be able to reduce such deleterious effects caused by insulin resistance. In view of the beneficial effects of liraglutide administration, these findings suggest that the use of liraglutide may be a promising therapy for AD with insulin-resistant condition.